Knowledge and Perception of Parents Towards Diet in Children With Autism - Ade Rosi; Chandra Isabella Hostanida Purba; Sri Hartati Pratiwi (Universitas Padjadjaran, 2019)
Gluten Free Casein Free (GFCF) is a diet recommendation to reduce hyperactivity in children with autism. Lack of adherence and knowledge can lead to improper dietary application which will result in remaining health problems and hyperactive behavior of autistic children. The purpose of this study is to examine knowledge and perception of parents towards GFCF diet in children with autism. This descriptive-quantitative study used a total sampling technique to 57 parents of autistic children in 3 Bandung District Extraordinary Schools. Data was obtained through questionnaire with validity ranging from 0.315-0.912 and reliability of 0.788 and 0.932. Data was analyzed using frequency and percentage in descriptive statistics. Results showed that some parents lacked of knowledge (n = 28), and 67% of subjects (n = 38) had a positive perception of GFCF diet. Positive perception includes perception of benefits, perception of susceptibility, perception of self efficacy, and perception of severity. In the perception of barrier, some subjects had negative perception. Based on the results, several parents had positive perception of GFCF diet, although the parental knowledge related to this diet was in the low category. That is likely because of parents have not received sufficient information related to GFCF diet. Therefore, health workers especially community nurses are expected to collaborate with nutritionists in making regular visits in order to provide parents of autistic children with health education related to GFCF diet in extraordinary schools.